Empowerment in Education: Collaboration Between Schools, Families, and Communities - ManArfa, Arman (JENDELA PENGETAHUAN, 2024)
Community empowerment in the education sector has become an important focus internationally to improve the quality and access of education for all individuals. A collaborative approach involving schools, families, and communities is an effective strategy for facing educational challenges. The role of society in the academic context is considered essential, goes beyond the boundaries of the classroom, and plays a vital role in supporting the educational process. Community empowerment refers to providing individuals and community groups the capacity to participate actively in the educational process. Collaboration between schools, families, and communities highlights the importance of viewing education as a shared responsibility. Family involvement in education significantly impacts children's academic development and achievement. Collaboration also involves the involvement of local communities as a valuable resource in supporting education. However, challenges such as gaps in the participation of parents from low economic backgrounds or minority groups require special efforts. Effective coordination and communication between various stakeholders are vital in planning and evaluating collaboration. A holistic and sustainable approach is needed to strengthen partnerships between schools, families, and communities to create an inclusive educational environment and stimulate students' holistic growth.